Mirabegron Alleviates the Degree of Burden Experienced by Caregivers of Older Females with Mixed or Urge Incontinence: A Prospective Study - Zachariou A (Dove Medical Press, 2021)
Athanasios Zachariou,1,2 Maria Filiponi,2 Aris Kaltsas,1,2 Fotios Dimitriadis,3 Ioannis Champilomatis,1 Athanasios Paliouras,1 Panagiota Tsounapi,4 Charalampos Mamoulakis,5 Atsushi Takenaka,4 Nikolaos Sofikitis1 1Urology Department, School of Medicine, Ioannina University, Ioannina, Greece; 2Incontinence Unit, Physical Medicine and Rehabilitation Centre EU PRATTEIN, Volos, Greece; 3 1st Urology Department, School of Medicine, Aristotle University, Thessaloniki, Greece; 4Urology Department, School of Medicine, Tottori University, Yonago, Japan; 5Urology Department, Medical School, University of Crete, Heraklion, GreeceCorrespondence: Athanasios ZachariouUrology Department, Ioannina University, 3 Spyridi Street, Volos, 38221, GreeceTel +306937227778Fax +302421026932Email zahariou@otenet.grPurpose: Older people, especially women, have the highest known prevalence of urinary incontinence (UI) of any other age-group. Continual care provision for elderly incontinent females is an incredibly arduous process, yet only very few studies have investigated the issue. Aim of the study was to evaluate the impact of mirabegron’s treatment on the degree of burden experienced by caregivers of elderly female patients with UI.Patients and Methods: A hundred and eighty-six caregivers of older females with mixed or urgency UI besides various conditions (strokes, post-operative recovery after major surgery, etc.) were included in the study. Group A comprised 91 patients that did not want to receive any treatment for UI. Group B consisted of 95 elderly females treated for UI with mirabegron 50 mg/daily for three months. All caregivers completed the Zarit Burden Scale (ZBS) questionnaire at the outset and after the three months. All patients completed a bladder diary at the beginning and at the end of the observation/medication period.Results: Patients receiving mirabegron presented a statistically significant improvement in UI parameters. Their caregivers showed a statistically significant decrease in the ZBS total score as well as separate domains.Conclusion: This pilot study confirms that mirabegron administration can improve the quality of life of older females suffering from UI while substantially relieving caregiver burden. Recognizing the physical and emotional reactions of caregivers may help health providers deliver better support and resources to meet the needs of caregivers and patients alike.Keywords: mirabegron, caregiver, Zarit Burden Scale, aging, incontinence